Factors affecting choice for education destination: A case study of international students at Universiti Utara Malaysia - Chew, Foo Chuan; Ismail, Russayani; Lim, Hock Eam (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
The importance of higher education services as a new source of income has intensified the effort not only by the developed nations but the developing countries alike, to offer their services to the international students. Most countries recognize that maintaining quality education is crucial as to ensure the long term competitiveness. Quality education signifies a very broad definition and it is vital for each country to correctly identify the factors that really attract international students to pursue their studies in particular places. With regard to the issue, this study attempts to identify the possible factors that may influence the decision making of international student when choosing higher education destination. In order to arrive at the result, we carry out the study by determining the factors that significantly influence the international students to recommend Universiti Utara Malaysia (UUM) to their friends in their home country. The study is conducted using a sample of 300 international students. The factor analysis and a regression using the logit model are used. The finding suggests that excellent services, pleasant social environment, first class physical infrastructure and high quality of lecturers matter.